2022
DOI: 10.3390/su14042346
|View full text |Cite
|
Sign up to set email alerts
|

Self-Regulation and Students Well-Being: A Systematic Review 2010–2020

Abstract: In recent years, there has been particular interest in studying the relationship between student self-regulation and variables such as students’ well-being, satisfaction, and school engagement. Although in other fields such as healthcare, self-regulation in different areas seems to influence individuals’ well-being, this is not so well established in the educational arena. We performed a systematic search of research articles published between 2010 and 2020 which explored the relationships between self-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 89 publications
2
12
0
3
Order By: Relevance
“…However, fewer studies have analyzed students' procrastination in educational stages prior to the university , despite the importance of this problem in secondary education (Klassen & Kuzucu, 2009;Ozer & Ferrari, 2011) and its close relationship with self-regulated learning (Schraw et al, 2007), a basic competence to develop in this educational stage (Albert, 2017;García-Ros et al, 2018a, Klassens, Krawchuk, & Hannok, 2011 that is closely related to students' academic performance (e.g., Dent & Koenka, 2016;Kitsantas et al, 2008;Pintrich & De Groot, 1990) and well-being (e.g., Litalien et al, 2013;Rodríguez et al, 2022). More specifically, Ozer (2011) showed the relevance of procrastination in secondary education, pointing out that more than half of the students in this educational stage procrastinate frequently, whereas Klassen and Kuzucu (2009) reveal that 83% procrastinate more than one hour per day, especially on postponing studying for exams (38% of students), performing weekly tasks (30%), and turning in work on time (27%).…”
Section: Introductionmentioning
confidence: 99%
“…However, fewer studies have analyzed students' procrastination in educational stages prior to the university , despite the importance of this problem in secondary education (Klassen & Kuzucu, 2009;Ozer & Ferrari, 2011) and its close relationship with self-regulated learning (Schraw et al, 2007), a basic competence to develop in this educational stage (Albert, 2017;García-Ros et al, 2018a, Klassens, Krawchuk, & Hannok, 2011 that is closely related to students' academic performance (e.g., Dent & Koenka, 2016;Kitsantas et al, 2008;Pintrich & De Groot, 1990) and well-being (e.g., Litalien et al, 2013;Rodríguez et al, 2022). More specifically, Ozer (2011) showed the relevance of procrastination in secondary education, pointing out that more than half of the students in this educational stage procrastinate frequently, whereas Klassen and Kuzucu (2009) reveal that 83% procrastinate more than one hour per day, especially on postponing studying for exams (38% of students), performing weekly tasks (30%), and turning in work on time (27%).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other authors had demonstrated the positive effect of the sense of belonging on mental well-being [29]- [31]. Likewise, there are prior studies that have documented the relationship between mental well-being and self-regulated learning observed in this study [38]- [41], [45].…”
Section: Discussionsupporting
confidence: 75%
“…Rodríguez et al [38] made a systematic review of the studies that analyzed the relationship between student well-being and self-regulated learning. They found that some self-regulation deficits are significantly associated with different dimensions of student well-being.…”
Section: Relationship Between Sense Of Belonging Sense Of Mattering A...mentioning
confidence: 99%
See 1 more Smart Citation
“…Upaya untuk mengatasi prokrastinasi akademik selain dengan bantuan teknik konseling CCT, regulasi diri dapat menjadi dorongan yang dapat memancing kemauan untuk menentukan tujuan hidup mengembangkan strategi dan merubah perilaku negativ yang dimunculkan (Faizah & Panduwinata, 2022) et al, 2021). Pendapat tersebut diperkuat oleh Susana Rodriguez dkk bahwa regulasi diri adalah penerapkan progress strategi dengan proses secara bertahap yang bertujuan untuk merubah dan mengevaluasi perilaku yang dimiliki (Rodríguez et al, 2022). Adapun faktor-faktor yang mendorong diri untuk melakukan regulasi diri yakni pertama menyadari dan memberikan penilaian atas perilaku maladaptif yang dilakukan, kedua memberikan reaksi secara efektif dikarenakan stimulus dari luar, ketiga mengobservasi diri dengan cara mencari hal yang menjadi permasalahan dalam diri, selanjutnya menata diri dengan planning tujuan hidup yang lebih positif (Sari & Wuri, 2019).…”
Section: "Ya Aku Manfaatkan Temenku Yang Pinterpinterkak Biar Ngajari...unclassified